Criticality and LCA – Building comparison values to show the impact of criticality on LCA - Koch, Björn; Peñaherrera, Fernando; Pehlken, Alexandra (European Journal of Sustainable Development, 2019)
Including criticality into Life Cycle Assessment (LCA) has always been challenging to achieve but desirable to accomplish. In this article, we present a new approach for the evaluation of resource consumption of products by building comparison values based on Life Cycle Impact Assessment (LCIA) combined with weighted criticality values to show the direct impacts of criticality on LCA results. For this purpose, we develop an impact indicator based on the Abiotic Depletion Potential (ADP) of natural resources and use the two main parameters defined by the EU to determine the criticality of a material - the economic importance and the supply risk – in our case studies to build the Criticality Weighted Abiotic Depletion Potentials (CWADPs), one for each parameter. These indicators allow identifying and measuring the impacts of criticality when comparing the results of resource depletion using the ADP methodology and the results that incorporate criticality. The comparison of the CWADPs to the corresponding EU criticality values and its thresholds it reflects the equivalent criticality of the assessed product. This information reflects the impacts of criticality on LCA and assesses the total resource consumption of critical materials in a system. Keywords: Life Cycle Assessment, criticality, resources, materials, sustainability indicator